(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2018)
An analytical approach is proposed to evaluate the bit error rate (BER) performance of a direct detection on-off keying (OOK) free space optical link over log-normal atmospheric turbulence-induced fading channels based on modified Alamouti code presented by Simon and Vilnrotter and maximal ratio combining (MRC) at the receiver. Simulations show that due to coding and diversity at the receiver, a significant improvement in the BER performance is obtained at a given BER. For diversity order of 2 in both transmitter and in receiver, the amount of BER improvement is 6.6dB at BER 10-5. Further increment of the receiver diversity from 2 to 4 gives additional 3dB improvement at the same BER. A drastic improvement of the BER performance is also possible for increasing number of receiver diversity which may increase hardware complexity. Simulation results are demonstrated to confirm the analytical results. Bangladesh J. Sci. Ind. Res.53(3), 205-210, 2018